Global supply chains and China’s textile cross-border trade: case study of Jiangsu province - Bitkova, T.; Chen, T. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
As one of the world’s largest producers and exporters of textiles and clothing, China plays a key role in the reconstruction of the global supply chain and in the changes in the international trade situation. China’s textile industry, as a traditionally profitable one, is facing unprecedented challenges and opportunities, which confirms the relevance of this study. The development of cross-border trade in textile products significantly depends on the business environment, which includes many factors, such as government support, prime cost, tariffs and external demand. Analyzing the impact of these factors on Chinese textile exports is a key focus of this study. Jiangsu Province is a home to numerous textile factories specializing in various products – from raw materials to finished garments. The province has a well-developed infrastructure, including ports, highways and railways, which facilitates the efficient movement of goods. Analyzing the impact of both domestic and international trade policies on textile industry may provide insights into the dynamics of cross-border supply chains. The paper focuses on sustainable practices in China’s textile industry that can improve the productivity and efficiency of supply chains. The study focuses on the impact of the international business environment on cross-border trade of Jiangsu Province. Through qualitative and quantitative data analysis on export demand, production costs, tariffs, exchange rates and policy support, the impact of these factors on the volume of cross-border trade in textiles and apparel is assessed. The paper proposes such strategies as improving the resilience of Jiangsu’s textile industry, optimizing production cost control, promoting innovation and upgrading of the industry with government support and enhancing the ability of enterprises to withstand trade risks. This can provide a sound basis for decision-making on industrial upgrading and expanding the global market for the textile industry of Jiangsu and other provinces in China.